Service robotics within the digital home applications and future prospects - González Alonso, Ignacio (Intelligent systems, control and automation: science and engineering, 2011)
This book provides the reader with a clear and precise description of robotics and other systems for home automation currently on the market, and discusses their interoperability and perspectives for the near future. It shows the different standards and the development platforms used by the main service robots in an international environment. This volume provides a scientific basis for the user who is looking for the best option to suit his or her needs from the available alternatives to integrate modern technology in the digital home.